Clinical Case Study of Psychological Picture of Patient with Oppositional Defiant Disorder - Alfeyni Ainun Nadlufatul Arifah; Nanda Audia Vrisaba (Department of Psychology, Faculty of Education, Universitas Negeri Surabaya, 2025)
Conduct disorders are often characterized by aggression and violation of other people's rights. Behavioral disorders are behaviors that involve problems in controlling emotions and behavior. This article presents a clinical case study of a 15-year-old patient with a primary diagnosis of behavioral disorder, which was later clarified as oppositional defiant disorder. The study aims to understand the patient's psychological profile by examining the patient's lifestyle through their social background, conducting a direct self-interview with the patient, obtaining information from the patient's close relatives, conducting structured interviews, observations, and reviewing psychological records over a one-month period. The findings were analyzed using Sigmund Freud's psychoanalysis of defense mechanisms, focusing on the suppression of emotions known as repression.